In vitro and in vivo studies on anti-withdrawal properties of Erythroxylum cuneatum (Miq.) Kurz leaf alkaloid extract - Ahmad Zaki, Muhammad Amin (2015)
Erythroxylum cuneatum (EC) is locally known as the ‘Chinta Mula’ plant. Its leaves are used by the native traditional healers as an anti-addiction treatment. However, its effects were not fully explored scientifically, resulting in lack of documented information on its therapeutic anti-addiction effects. The objectives of this study are to produce a standard extract of EC, examining the efficacy of alkaloid extract of EC on cyclic adenosine monophosphate (cAMP) production in SK-N-SH cell after chronic morphine treatment and to investigate the effect of EC extract on anti-withdrawal properties in the morphineaddicted rats. The alkaloid crude extract of EC underwent two extraction processes, namely the Soxhlet and the acid-base extraction. The alkaloid crude extract of EC was obtained using acid-base extraction and the yield was 0.19% from 1 kg leaves. The invitro studies was performed separately as two different tests (co-treatment and pretreatment) whereas in-vivo study used 6 groups (n=8) of Wistar rats (male: 180-220 g) which were treated with morphine at 10-30 mg/kg for 5 consecutive days. Withdrawal signs exhibited by the morphine-dependent rats were measured by 9 counts and checking of parametric signs. The rats were then treated with two different interventions which are Methadone (5 mg/kg), and crude alkaloid extract of EC (5, 25 and 50 mg/kg) respectively and the withdrawal signs were re-evaluated again. Co-treatment for 24 h between morphine sulphate with alkaloid extract of EC significantly reduced (p<0.05) the production of cyclic AMP at lower concentration (0.1 mg). Similarly pre-treatment with morphine sulphate for 24 h then treated with alkaloid extract of EC for 6 h significantly reduced the production of cyclic AMP (P<0.05). In-vivo results also showed that administration of alkaloid extracts of EC caused significant reduction (p<0.05) in all withdrawal signs. The results obtained from the study suggested that the administration alkaloid extract of EC caused significant decrease in the withdrawal signs of morphine addicted both in vitro and in vivo studies.